2014
DOI: 10.1111/hsc.12107
|View full text |Cite
|
Sign up to set email alerts
|

‘When coercion moves into your home’ - a qualitative study of patient experiences with outpatient commitment in Norway

Abstract: The use of coercion on people with mental illness is a serious intervention, and a reduction in its use is a declared goal in mental health care. Yet many countries have introduced expanded powers of coercion in recent years, including outpatient commitment (OC). However, the evidence of the effectiveness of OC is inconclusive, and little is known about how patients experience OC schemes. The objective of this qualitative study was to explore (1) patients' experiences with OC, and (2) how routines in care and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 23 publications
6
51
1
2
Order By: Relevance
“…Yet, both studies showed that most patients were positive about their OC order, because the OC structure allowed them to develop. Riley et al (2014) found that patients adapted to OC even though they did not want the scheme. In the studies by Gibbs et al (2005), O'Reilly et al (2006), and Riley et al (2014), patients compared OC to previous compulsory hospitalization and thus experienced greater autonomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, both studies showed that most patients were positive about their OC order, because the OC structure allowed them to develop. Riley et al (2014) found that patients adapted to OC even though they did not want the scheme. In the studies by Gibbs et al (2005), O'Reilly et al (2006), and Riley et al (2014), patients compared OC to previous compulsory hospitalization and thus experienced greater autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies show that patients experience greater autonomy and appreciate the structure, support, and follow-up, but experience little influence on their treatment, reduced choices in housing, and restrictions on travel (Gibbs, Dawson, Ansley, & Mullen, 2005;O'Reilly, Keegan, Corring, Shrikhande, & Natarajan, 2006;Ridley & Hunter, 2013). Riley, Høyer, and Lorem (2014) showed that patients feel that their freedom is restricted, and that they only agree to OC because they consider it better than compulsory hospitalization. Both Gault, Gallagher, and Chambers (2013) and Hughes, Hayward, and Finlay (2009) found that a caring, supportive relationship reduced patients' feeling of coercion under OC.…”
mentioning
confidence: 99%
“…Many find some aspects of the order helpful, while other aspects restrict their lives in ways that can be highly problematic. [13][14][15][16][17][18] The highest priority for all 3 groups is usually to avoid hospital admission. 16 It is worth noting that the experienced advantages of CTO often are expressed by way of comparison with detention in hospital, not with receiving comprehensive community services voluntarily.…”
Section: Descriptive Studiesmentioning
confidence: 99%
“…Increased input into decision-making was reported by some consumers at later stages of the CTO process, including reviews, as well as other care planning decisions (such as preferences for support options during crisis) [48, 53]. One study reported on the lack of impact of advance directives as a means for increased consumer participation, with consumers reporting that their statements were ignored [25].…”
Section: Core Components Of Case Managementmentioning
confidence: 99%
“…Whilst some consumers reported a ‘blurred distinction between formal and informal coercion’ with treatment pressure a usual experience of mental health care (p.6) [43], others on CTOs experienced contact with mental health services to be more intrusive and coercive than the same contact had been experienced prior to the CTO [53, 58, 59]. The use of persuasion was found to be more common for those on CTOs and resulted in significantly higher levels of perceived coercion.…”
Section: Core Components Of Case Managementmentioning
confidence: 99%